The Effect of Foliar Feeding on the Biometric Indicators of Winter Wheat Varieties - F. I, Toshkentboeva; Sh. S, Abriev (American Journal of Biology and Natural Sciences, 2026)
The research results showed that compared to the variant fertilized at the generally accepted norm, the application of a suspension of urea and micronutrients leads to the formation of plants with spike lengths 0.5–0.9 cm longer, depending on the variety and the type of micronutrients used.